The Effect Of Financial Literacy, Investment Motivation and Financial Behavior On Investment Interest - Septia Tri Utari; Wira Ramashar; Mentari Dwi Aristi (Asosiasi Dosen Akuntansi Indonesia, 2022)
This study aims to determine the effect of financial literacy, investment motivation and financial behavior on students' interest in investing. The population in this study were students of the Muhammadiyah Riau University accounting study program class of 2018-2019. The sampling technique in this study used a probability sampling technique with a total of 84 students. The results of this study indicate that (1) financial literacy has a significant effect on student interest in investing, (2) investment motivation has a significant effect on student interest in investing, and (3) financial behavior has a significant effect on student interest in investing.